Different Causes Of Skin Allergy And Their Management In Ayurveda - Meena, Jaikishan; Panja, Asit K; Meena, Shashi bala (International Research Journal of Ayurveda & Yoga, 2020)
The word “allergy” is derived from the ancient Greek word allos meaning “other” and ergon meaning “work”. Allergy is one of four forms of the hypersensitivity and is formally called as type (or immediate) hypersensitivity. When some allergens are responsible for triggering an immune system response, then it is said to be as allergic skin condition. Irritated skin can be caused by different factors which include immune system disorders, infections (10%), food (35%), cosmetics, drugs (6%) and pollution. 20-30 % of the Indian population is suffering from this disease. Allergic reactions are distinctive because of excessive activation of certain white blood cells called mast cells and basophil by a type of antibody called immunoglobulin E (IgE).In Ayurveda, allergic manifestation is mentioned under the concept of Satmya and Asatmya. It manifests due to exposure to Asatmya Aahara -Vihara and contact with different poisonous material (allergens) called as Dushi Visha in Ayurveda. Symptoms of allergic skin reaction are descried as separate chapter under the title of Sheetpitta, Udarda and Kotha.In modern science vast treatment of Urticaria and other allergic skin disorders is present but recurrence of the disease is very common. Ayurveda demonstrates a great potential in the treatment of allergic skin disorders. This paper will detail the above-mentioned concepts in elaboration.